The Influence of Early Childhood Education on the Learning Achievement of Class I Elementary School Students in Mataram City - Dianti, Ira (JUPE : Jurnal Pendidikan Mandala, 2024)
This research refers to the phenomenon of early childhood education and the lifestyle behavior of children aged 0-6 years who will receive formal education before entering elementary school.This early childhood education continues the education whose foundations have been laid by parents in the family. Children or elementary school students who attend early childhood education achieve better than students who do not receive early childhood education in the city of Mataram. This research aims to determine the level of difference in learning achievement of grade I elementary school students, students who have attended early childhood education (formal) and students who have not attended formal education (non-formal/informal) in Mataram City. The research method usesqualitative approach. This type of research is descriptive, data collection methods are observation, interviews and documentation. Interviews were conducted with class I teachers and students' parents. The research results show thatElementary school students who take part in early childhood education achieve better than students who do not take part. This achievement is not only in the intellectual aspect, but also the psychomotor aspect, values and attitudes of grade 1 students in Mataram City